Impact of Ability, Motivation and Work Discipline on Staff Performance - Hafid Cahyanto; Tanto G Sumarsono; Mokhamad Natsir (Innovation Business Management and Accounting Journal, 2024)
This research aims to describe the work abilities, work motivation, work discipline, and performance of Air Base (Lanud) Abd. Saleh Military security staff. Saleh Analyzes the significance level of the influence of workability, work motivation, and work discipline simultaneously, partially, and dominantly on the performance of Air Base (Lanud) Abd. Saleh Military security staff. This research includes quantitative research with comparative causal and explanatory research types. This research was conducted at Air Base (Lanud) Abd. Saleh. The choice of location for this research is based on the place studied because there has yet to be research on the influence of Ability, motivation, and discipline on the performance of Air Base (Lanud) Abd. Saleh Military security staff. Saleh Malang. The population comprised 155 enlisted members, non-commissioned officers, and first officers. The sample calculation for this study used the Slovin formula with a simple formula, so after calculating it using the Slovin formula according to Sugiyono 2011, a sample of 155 samples was obtained. The data analysis technique used is the descriptive analysis technique. Next, analysis is carried out using multiple linear regression analysis to find the influence between the independent variable (X) and the independent variable (Y). The research results show that work ability, work motivation, and work discipline significantly affect the performance of Air Base (Lanud) Abd. Saleh Military security staff. Workability, work motivation, and discipline in responding quickly to instructions positively impact staff performance by completing work on time. Work skills are needed when working as Air Base (Lanud) Abd. Saleh Military security staff, all staff must have high work motivation for this reason.